Public management practices and IT Driven Culture Approaches - Dash, Priyabrat (International Journal of Psychosocial Rehabilitation, 2019)
The paper’s primary objectives are: to define and examine the main ways in which corporate management practices and techniques can be adjusted to function in the sense of an IT-driven society, to decide which were the best ways for managers to deal with the challenges of managing global teams, to evaluate new guidelines to handle these crises in the modern digital workplace. In terms of meaningful results and assumptions, it is necessary to note those concerning the need to form a range of new management practices and techniques capable of validating the real needs of the current social and economic context in which organizations operate, and the reality that the traditional way in which the management process takes place is no longer sufficient. The paper also provides a set of basic principles to be adopted in terms of defining current management patterns and strategies in the globalized society guided by IT, which today’s practitioners could use when creating their own game rules, based on the particular context. Given the complexities of the world, more work should be regarded and undertaken with a view to better understanding how executives need to act in order to truly profit their companies from the benefits of information technology